PERAN EVALUASI SUMATIF DALAM MENGUKUR CAPAIAN PEMBELAJARAN - Suniati; Moh. Sahlan (PT. Hasba Edukasi Mandiri, 2026)
Summative evaluation is an essential component of the learning process that serves to measure the achievement of learning objectives and students' learning outcomes at the end of an instructional period. This study aims to describe the concept of summative evaluation and analyze its role in measuring students' learning achievements. The study employed a qualitative approach using the library research method. Data were collected through a review of various sources, including books, scientific journal articles, educational policy documents, and government regulations related to educational evaluation. Data analysis involved data reduction, data presentation, content analysis, and conclusion drawing. The findings indicate that summative evaluation plays a significant role in measuring students' competency attainment, determining the achievement of learning objectives, assigning final grades, determining learning mastery, preparing learning outcome reports, providing feedback for teachers to improve instructional quality, and supporting evidence-based educational policymaking at the school level. To ensure that evaluation results accurately reflect students' competencies, the implementation of summative evaluation should adhere to the principles of validity, objectivity, fairness, reliability, and accountability. Therefore, summative evaluation functions not only as an instrument for assessing learning outcomes but also as a strategic tool for improving the quality of instruction and fostering continuous educational improvement.